Analisis Kesalahaan berbahasa dalam bidang morfologi pada karangan narasi siswa kelas VI SD 1 Lau - Cahyani, Linda Dwi; Apriliana, Winny; Setiawaty, Rani (FKIP, PGSD, Universitas Slamet Riyadi, 2025)
This study aims to identify the analysis of language errors in the field of morphology in the narrative essays of 6th grade students at SD 1 Lau. This approach uses a qualitative, descriptive research approach. This type of research is qualitative research with descriptive methods. Data collection of words and sentences containing language errors in the field of morphology in the narrative essays of grade VI students of SD 1 Lau was carried out by observing and using the documentation method and simak catat. Based on the results of the identification of errors that have been obtained, they are then processed through technical data analysis work. Data obtained by reading each essay of grade VI students and noting the use of incorrect language. Based on the results of the study, it shows that grade VI students of SD 1 Lau still experience errors in writing student narrative essays. These errors are: errors in writing prepositions; errors in using the prefix ke-; errors in using the prefix di-; errors in writing the suffix -nya; errors in writing the suffix -an; errors in omitting the suffix -i; errors in using the confix or simulfix men; errors in using the confix or simulfix ber; and errors in writing reduplication.